The Influence of Quality Audit on Management Accountability in Plantation Companies in Indonesia - Zufrizal; Nurhayati (Jurnal Ilmiah Akuntansi Kesatuan, 2026)
Transparency and integrity in financial reporting within the agribusiness sector are essential, particularly in the recognition of biological assets in accordance with PSAK 69. This study aims to analyze the influence of audit quality on management accountability in plantation companies in Indonesia. This study uses an explanatory quantitative approach with a sample of 35 public plantation companies and state-owned enterprises during the 2020–2024 period. Secondary data is obtained from audited financial statements, annual reports, and sustainability reports. The analysis was performed using multiple linear regression. The results of the study show that audit quality has a positive and significant effect on management accountability, which is reflected in increased transparency in reporting biological assets, crop yields, and compliance with corporate governance principles. In addition, company size and profitability strengthen accountability, while leverage has a negative influence. This research confirms that high-quality audits play an important role in strengthening the governance and sustainability of the plantation sector in Indonesia.